The effects of macroeconomic shocks on employment: The case of Mexico - Campos Vázquez, Raymundo M. (Estudios Económicos de El Colegio de México, 2010)
This paper studies the effects of macroeconomic shocks in employment and wages for the case of Mexico. I find that young and unskilled workers are the most affected by an economic shock in terms of unemployment, labor force participation and employment in the informal sector. I derive a theoretical model to study the effects of macroeconomic shocks on wages and employment composition. The theoretical findings imply that the elasticities of labor supply in the formal and informal sector are close to 0.75 and 0 respectively, and both labor demand elasticities are close to 1.